Phenotypic characterization of indigenous sheep breeds in the Jimma Zone, Oromia, Ethiopia - Yaregal Derbie; Hailu Tilahun (Journal of Applied Animal Research, 2023)
The objective of the study was to undertake phenotypic characterization of sheep, in their production environment. A total of 570 sheep were used in this study for body measurements. After the data were collected, using the Proc GLM model, quantitative data were analysed by SAS version 9.3 (2014) and qualitative data were analysed by SPSS. The dominant coat colour pattern observed was 81.1% plain, 16.4% patchy and sheep with spotted pattern (2.5%), respectively. Brown (43.5%), fawn (17.5%) and red (13.0%) were the most frequently observed coat colour types. The majority (91.1%) of sheep were polled whereas (8.9%) of the sheep were horned. The effect of the district on body weight and most of the linear body measurements were significant (p < 0.05) except head length, canon bone length, ear length and tail length. Chest girth explains more variation than any other linear body measurements in both ewes (94%) and rams (93%). The prediction of body weight based on regression equation y = −21.82 + 0.68x for female sheep and y = −49.90 + 1.08x for male sheep, where y and x are body weight and chest girth, respectively. In general, it could help as an input for efficient utilization, conservation and improvement in the future.